Factors affecting the development of airflow limitation among South Korean smokers - Kim, Youngmee (Tob Induc Dis, 2019)
INTRODUCTION: Considering that only some and not all smokers develop chronic obstructive pulmonary disease (COPD), there may be other factors responsible for the development of COPD among smokers. Previous researchers have reported that ethnicity could be one of factors associated with the development of COPD. This study aimed to examine the factors associated with the development of airflow limitation, suggestive of having COPD, among Korean smokers using data from the Korea National Health and Nutrition Examination Survey conducted over the past 3 years. METHODS: A total of 2569 current and former smokers ≥40 years of age were included. Most studies exploring risk factors for COPD have compared smokers and non-smokers with smoking as only one of the independent variables. In this study, we took a different approach, studying only smokers and comparing those with or without airflow limitation. RESULTS: The prevalence of airflow limitation among the study participants was 19.2% and 22.1% in current and former smokers, respectively. There was no significant correlation between the severity of airflow limitation and total lifetime smoking amount. Among the many variables examined, only age, male gender and total lifetime smoking amount (pack-years) were significant factors associated with the development of cigarette smoke-induced airflow limitation. CONSLUSIONS: Older Korean men who are heavy smokers may be at a higher risk of developing COPD. Our findings support the importance of smoking cessation as the best way to prevent the development of COPD.